Engagement, communications and capacity building for climate change adaptation - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
CCAFS strives to engage with stakeholders regularly and bridge networks by using innovative communication tools to disseminate science-based evidence from research and also to understand how perceptions and feedback from the ﬁeld can be integrated into research.